Analisis Kinerja Private Cloud Computing Menggunakan Metode Reability, Maintanability, Availability dan Security - Rahmad Kartolo; Edi Surya Negara (P3M Politeknik Negeri Bengkalis, 2022)
SMK Negeri 2 Palembang is a school based on technology techniques, the technology used is cloud computing, measurements using the RMA method performance analysis testing using the RMA scanning method were carried out on peak hours from 08.00-10.00 am obtained the availability level of ping sensors is 43.09%, http sensors are 25.32%, imap sensors are 30.8%, pop3 sensors are 36.1% then ping jitter sensors are obtained 61.4%, From the results of monitoring with a percentage of the measurement table from various sensors during peak hours, there are several sensors that have decreased, such as imap and http sensors with availability values of 30.8% and 25.32% so that it affects sensor performance so that a total of 196.71% is classified as Sufficient. tomudian on the security side obtained scanning results using Owasp ZAP Vulnerability is 8 Alerts consisting of 3 medium level risks, 2 low risk levels and 3 risk level information and scanning using NESSUS obtained vulnerabilities, namely: Http server / web server version, scanner port, Based on the results of the analysis that network traffic is very vulnerable at 08.00-10.00, so to get a more stable quality, users should access it at 13.00 – 15.00 then on security issues to minimize security gaps can add proxies to the web, upgrade libraries, activate ip and ports filter, upgrade http sever.Keywords - RMA, Private Cloud, Nessus, Owasp ZAP.